Archimedes' Principle Applied to Buoy Design for Measuring Purposes in Offshore Illumination Conditions - Rizki Aulia Nanda; Karyadi Karyadi; Fathan Mubina Dewadi; Amir Amir; Mohamad Rizkiyanto (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2022)
Solar cells are becoming so common that every industry except PLN is already using them to produce alternative energy. The more solar cells used, the more light intensity meters are needed to calculate the amount of Illumination in a given area. This research entails constructing or implementing software, calculating the float's balance against the impact of waves, and determining how the float distributes load using the Archimedes principle. Electrical construction and chassis buoyancy are included in the design. When the density of water is greater than the density of the object, namely > objects (997 kg/m3 > 46.73 kg/m3), the variables obtained are the total weight of the buoy of 5,044 kg with the distribution of the object force of 49.43 N and the buoyant force of 1046.08 N. then this design produces the required buoyancy force when manufactured and used.